(untitled) (Journal of Guidance and Counselling Studies, 2023)
The emerging issues in educational, social, and psychological spheres in Nigeria today provide the basis for undertaking research in order to combat them. The various ways to mitigate the prevailing issues, among others, is to promote religious tolerance. In this paper, religious tolerance is defined as the acceptance of religious pluralism. Its underlying causes which include illiteracy and ignorance, poverty, over-ambition, exaggerated sense of self-worth and pride, political and territorial ambitions, expressions of bigotry, stereotypes, stigmatization, insults and lack of access to social justice and corruption have been highlighted. The functions of religion as a unifying factor for sustainable development have been analyzed. The paper has also discussed strategies for addressing religious intolerance. They include provision of quality and moral education, interaction with people of different faiths and backgrounds, access to information, personal awareness, enforcement of human rights through legislation and punishments, and local solutions through dialogue and negotiations. The paper suggested establishment of faith or religious agency for inter-religious faiths discussions, dialogue and peaceful coexistence, advocacy and reorientation programmes, and policy direction by government at all levels to monitor and control religious activities, among others.